2015
DOI: 10.3390/ijms161226179
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin Suppresses RANKL-Mediated Osteoclastogenesis through Inhibition of MAPKs and NF-κB

Abstract: Calycosin, an isoflavonoid phytoestrogen, isolated from Radix Astragali, was reported to possess anti-tumor, anti-inflammation, and osteogenic properties, but its impact on osteoclast differentiation remains unclear. In this study, we examined the effects of calycosin on osteoclastogenesis induced by RANKL. The results showed that calycosin significantly inhibited RANKL-induced osteoclast formation from primary bone marrow macrophages (BMMs). Calycosin also dose-dependently suppressed the formation of bone res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…It has been reported that specific genes, such as cathepsin K, MMP-9, and TRAP, are upregulated in response to RANKL [25][26][27]. Our results demonstrated that the expression of these osteoclastspecific genes was increased by RANKL, and IL-35 enhanced such gene expression similarly to other cytokines including IL-17 and IL-15 [28,29].…”
Section: Discussionsupporting
confidence: 60%
“…It has been reported that specific genes, such as cathepsin K, MMP-9, and TRAP, are upregulated in response to RANKL [25][26][27]. Our results demonstrated that the expression of these osteoclastspecific genes was increased by RANKL, and IL-35 enhanced such gene expression similarly to other cytokines including IL-17 and IL-15 [28,29].…”
Section: Discussionsupporting
confidence: 60%
“…Calycosin reduced NF‐κB activation in TNF‐α‐stimulated 16HBE cells or LPS‐stimulated human keratinocytes . Calycosin inhibits the phosphorylation of ERK 1/2 and NF‐κB . Hence, calycosin may also regulate the expression of HIF‐1α by transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Calycosin, an isoflavonoid phytoestrogen isolated from Astragali Radix, was reported to possess antitumour and anti‐inflammation properties . The dried roots of Astragali Radix, called “Huang Qi” in Chinese, are well known as a basic traditional Chinese medicine for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…On the fifth day after seeding, the cells were incubated with 5% (vol/vol) NaClO 3 for 5 min at room temperature to remove the cells. As described in the modified Von Kossa method (Quan et al, ; Xu et al, ), 5% (wt/vol) AgNO 3 was added and incubated at room temperature for 1 h in the dark. Subsequently, 10% formaldehyde and 5% (wt/vol) Na 2 CO 3 were added to the cells and incubated at room temperature for 5 min, following which the cells were washed five times with water.…”
Section: Methodsmentioning
confidence: 99%